2011
DOI: 10.1038/emboj.2011.271
|View full text |Cite
|
Sign up to set email alerts
|

The structure of a transcription activation subcomplex reveals how σ70is recruited to PhoB promoters

Abstract: PhoB is a two-component response regulator that activates transcription by interacting with the r 70 subunit of the E. coli RNA polymerase in promoters in which the À35 r 70 -recognition element is replaced by the pho box. The crystal structure of a transcription initiation subcomplex that includes the r 4 domain of r 70 fused with the RNA polymerase b subunit flap tip helix, the PhoB effector domain and the pho box DNA reveals how r 4 recognizes the upstream pho box repeat. As with the À35 element, r 4 achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
71
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 56 publications
9
71
0
Order By: Relevance
“…PhoB E has a winged-helix motif for DNA binding, where helix α 3 is the recognition helix. Between helices α 2 and α 3 within the modified helix-turn-helix motif, there is a seven-residue loop which has been named the transactivation loop because it was postulated to interact with the σ 70 subunit to activate transcription (Makino et al , 1996 ;Blanco et al , 2002 ); we recently confirmed this theory with the crystallographic structure of a ternary complex formed by the PhoB E dimer, a pho box DNA and the σ 4 domain of σ 70 (Blanco et al , 2011 ). In the present structure, a tandem of two protomers arranged head-to-tail sits at one side of the DNA molecule, the recognition helices α 3 lay along the major groove while the wing tips contact the downstream minor groove, performing specific (with bases) and nonspecific (with phosphates) interactions ( Figure 3B).…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…PhoB E has a winged-helix motif for DNA binding, where helix α 3 is the recognition helix. Between helices α 2 and α 3 within the modified helix-turn-helix motif, there is a seven-residue loop which has been named the transactivation loop because it was postulated to interact with the σ 70 subunit to activate transcription (Makino et al , 1996 ;Blanco et al , 2002 ); we recently confirmed this theory with the crystallographic structure of a ternary complex formed by the PhoB E dimer, a pho box DNA and the σ 4 domain of σ 70 (Blanco et al , 2011 ). In the present structure, a tandem of two protomers arranged head-to-tail sits at one side of the DNA molecule, the recognition helices α 3 lay along the major groove while the wing tips contact the downstream minor groove, performing specific (with bases) and nonspecific (with phosphates) interactions ( Figure 3B).…”
mentioning
confidence: 59%
“…σ 70 is formed by three structural domains ( σ 2 , σ 3 and σ 4 ), the C-terminal region ( σ 4 ) being the one that recognizes the -35 element and hence the putative PhoB E target for activating transcription (Makino et al , 1993 ;Kumar et al , 1994 ). In a recent study we provided crystallographic evidence that the DNA-bound PhoB E domain directly contacts the σ 4 domain of σ 70 to accomplish RNA polymerase recruitment (Blanco et al , 2011 ). Here we complement this finding with biochemical data on the PhoB mode of binding to natural promoters containing multiple pho boxes and report a new σ -free crystal structure of the PhoB E dimer bound in tandem to a 26-mer DNA comprising the pho box promoter sequence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To better understand the roles of the REC-DBD interface in transcription activation, we dock the E. coli RNAPH 18 to the PmrA-DNA complex structure on the basis of the crystal structure of the s 4 -b-flap tip helix chimer/PhoB-DBD/DNA ternary complex 29 (Supplementary Fig. 14).…”
Section: Discussionmentioning
confidence: 99%
“…3d) (Benoff et al, 2002) or PhoB at pho box DNA (Fig. 3f) (Blanco et al, 2011), the activator is poised to interact with a common set of region 4 residues (discussed by Bonocora et al, 2008). However, the particular positioning of BvgA~P at P fim3 means that these residues are not available for a region 4/activator interaction.…”
Section: Phase Variation In the Fim Genes Generates Phenotypic Diversmentioning
confidence: 99%